Stigma reducing components of direct-to-consumer advertising: theory-driven content analysis of print direct-to-consumer advertising - Kang, Hannah (Kansas State University, 2009)
Since the Food and Drug Administration (FDA) relaxed regulations on broadcast DTC advertising in 1997, DTC advertising has become a prominent part of public health communication. The purpose of this study is to assess the stigma reducing components of DTC ads based on the attribution theory and recategorization theory. Taken together, the combination of these two health communication theories can provide a useful framework to assess whether DTC advertising has made a sufficient effort to reduce the barrier in an attempt to motivate people to take appropriate actions for their treatment. A content-analysis of the past ten years from 1998 to 2008 of DTC ads of stigmatized diseases was done to critically evaluate the practice of DTC ads. Results focus on the prevalence of onset controllability (e.g., whether contracting an illness is blamable or not), offset responsibility (e.g., whether people have efforts to cope with or not) and recategorization (e.g., in-group) as textual cues and visual cues in the ads. Only half of ads (57%) offered a stigma reducing strategy. The most prevalent for both textual cues and visual cues were recategorization. However, an unbalance of stigma reducing components implies a meaning that Corrigan and Penn (1999)’s strategy of interventions to reduce stigma could not effectively function. Therefore, it required appropriate adjustments by onset controllability, offset responsibility and recategorization.
Keywords: DTC advertising; Education, Social Sciences (0534)